Anti‐IL‐23 and Anti‐IL‐17 Biologic Agents for the Treatment of Immune‐Mediated Inflammatory Conditions. Issue 1 (19th October 2017) - Frieder, Jillian; Kivelevitch, Dario; Haugh, Isabel; Watson, Ian; Menter, Alan
Abstract : Advancements in the immunopathogenesis of psoriasis have identified interleukin (IL)‐23 and IL‐17 as fundamental contributors in the immune pathways of the disease. Leveraging these promising therapeutic targets has led to the emergence of a number of anti‐IL‐23 and ‐17 biologic agents with the potential to treat multiple conditions with common underlying pathology. The unprecedented clinical efficacy of these agents in the treatment of psoriasis has paved way for their evaluation in diseases such as psoriatic arthritis, Crohn's disease, rheumatoid arthritis, in addition to other immune‐mediated conditions. Here we review the IL‐23/IL‐17 immune pathways and discuss the key clinical and safety data of the anti‐IL‐23 and anti‐IL‐17 biologic agents in psoriasis and other immune‐mediated diseases.